"Thermoeconomics": Time to move beyond the second law. (December 2020) - Corning, Peter A.
Abstract: The term "thermoeconomics" denotes a paradigm shift in our understanding of the role of energy in living systems, and in evolution. It is based on the proposition that energy in biological evolution can best be defined and understood, not in terms of the Second Law of Thermodynamics but in terms of such economic criteria as productivity, efficiency, and especially the costs and benefits (or "profitability") of various mechanisms for capturing and utilizing energy to build biomass and do work. Thus, thermoeconomics is fully consistent with contemporary evolutionary theory. Functional criteria provide a better explanation of the advances (and recessions) in bioenergetic technologies in evolution than does any formulation derived from the Second Law. Highlights: The many thermodynamic approaches to evolution are critically reviewed. Some of the contradictions and paradoxes are highlighted. Contrary to a Second Law approach, the key role of energy is emphasized. The importance of economic criteria, especially "profitability", is stressed. "Maxwell's demon" provides an illustration of this alternative paradigm.